2004
DOI: 10.1111/j.1048-891x.2004.014213.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Muslim women less susceptible to oncogenic human papillomavirus infection? A study from rural eastern India

Abstract: Muslim women are known to have lower incidences of cervical cancer and/or human papillomavirus (HPV) infection. Here we aim to determine any association that may be present between the oncogenic HPV16/18 infections and abnormal cytological lesions along with demographic and other attributes among Indian Muslim women (n = 478) and compare with the neighboring Hindus (n = 534) from a prospective cohort study. Agewise distribution of both subject-groups is similar. HPV16/18 infection is present in 9.6% Muslims an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
9
23
1
Order By: Relevance
“…High-risk HPV types 16 and 18 were detected in 8.2% of the entire sample and in 22% of the samples positive for HPV DNA types 6, 11, 16, 18, 31 and 33, using consensus primers. The prevalence of HPV 16/18 in the index study, is consistent with that reported by Duttagupta et al [20] Probable incrementing factor for the high prevalence of HPV DNA is poor hygiene. It is corroborated by the observation that a significant number, i.e., 58% of positive women had vaginitis.…”
Section: Discussionsupporting
confidence: 91%
“…High-risk HPV types 16 and 18 were detected in 8.2% of the entire sample and in 22% of the samples positive for HPV DNA types 6, 11, 16, 18, 31 and 33, using consensus primers. The prevalence of HPV 16/18 in the index study, is consistent with that reported by Duttagupta et al [20] Probable incrementing factor for the high prevalence of HPV DNA is poor hygiene. It is corroborated by the observation that a significant number, i.e., 58% of positive women had vaginitis.…”
Section: Discussionsupporting
confidence: 91%
“…Most previous surveys in developing countries (Duttagupta et al, 2004), including those by IARC, had to rely on locally read cytology and indeed showed a much lower agreement between cytological findings and HPV results than in our present study, where 85% of moderate and severe dyskaryosis (corresponding to high-grade squamous intraepithelial lesions, HSIL) harboured high-risk HPV types. Moderate or severe dyskaryoses were never found below 25 years in Dindigul District, but their prevalence increased with age and in women aged 45 or older it was approximately four-fold greater than in women in the same age group in England (Department of Health, 2000).…”
Section: Papillomavirus In Rural India S Franceschi Et Alcontrasting
confidence: 90%
“…The combined prevalence in a rural area of West Bengal of HPV types 16 and 18 in 534 Hindu women and 478 Muslim women was 7.5 and 9.6%, respectively (Duttagupta et al, 2004). HPV 16 and 18 positivity was similar in four age groups (o25, 25 -34, 35 -44, X45 years) among Muslim women, but steeply declined with age among Hindu women.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, in Bali a significant decline in HPV prevalence with increasing age was seen, as in some western countries, in Korea and among Hindu women in India (Duttagupta et al, 2004). In the latter, the reproductive period (and thus active sexual life) of Hindu women mostly ends by the age of 30 -35 years, which could explain the decreasing prevalence observed.…”
Section: Discussionmentioning
confidence: 80%